Answer:
(- 3, 37) and (-
,
)
Step-by-step explanation:
Given the 2 equations
2x² - y + 19 = 0 → (1)
y + 11x = 4 → (2) ← subtract 11x from both sides
y = 4 - 11x → (3)
Substitute y = 4 - 11x into (1)
2x² - (4 - 11x) + 19 = 0
2x² - 4 + 11x + 19 = 0
2x² + 11x + 15 = 0 ← in standard form
(2x + 5)(x + 3) = 0 ← in factored form
Equate each factor to zero and solve for x
2x + 5 = 0 ⇒ 2x = - 5 ⇒ x = - ![\frac{5}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B2%7D)
x + 3 = 0 ⇒ x = - 3
Substitute these values into (3) for corresponding values of y
x = -
: y = 4 +
=
⇒ (-
,
)
x = - 3 : y = 4 + 33 = 37 ⇒ (- 3, 37 )